Staphylococcus ratti sp. nov. Isolated from a Lab Rat - Kovařovic, Vojtěch; Sedláček, Ivo; Petráš, Petr; Králová, Stanislava; Mašlaňová, Ivana; Švec, Pavel; Neumann-Schaal, Meina; Botka, Tibor; Gelbíčová, Tereza; Staňková, Eva; Doškař, Jiří; Pantůček, Roman (Pathogens (Basel, Switzerland), 2022)
Staphylococci from the Staphylococcus intermedius-Staphylococcus hyicus species group include numerous animal pathogens and are an important reservoir of virulence and antimicrobial resistance determinants. Due to their pathogenic potential, they are possible causative agents of zoonoses in humans; therefore, it is important to address the properties of these strains. Here we used a polyphasic taxonomic approach to characterize the coagulase-negative staphylococcal strain NRL/St 03/464T, isolated from the nostrils of a healthy laboratory rat during a microbiological screening of laboratory animals. The 16S rRNA sequence, MALDI-TOF mass spectrometry and positive urea hydrolysis and beta-glucuronidase tests clearly distinguished it from closely related Staphylococcus spp. All analyses have consistently shown that the closest relative is Staphylococcus chromogenes; however, values of digital DNA-DNA hybridization <35.3% and an average nucleotide identity <81.4% confirmed that the analyzed strain is a distinct Staphylococcus species. Whole-genome sequencing and expert annotation of the genome revealed the presence of novel variable genetic elements, including two plasmids named pSR9025A and pSR9025B, prophages, genomic islands and a composite transposon that may confer selective advantages to other bacteria and enhance their survival. Based on phenotypic, phylogenetic and genomic data obtained in this study, the strain NRL/St 03/464T (= CCM 9025T = LMG 31873T = DSM 111348T) represents a novel species with the suggested name Staphylococcus ratti sp. nov.
Keywords: Hyicus-Intermedius species group; whole genome sequencing; variable genetic element; genomic island; taxonomy; Staphylococcus; laboratory rat